2006
DOI: 10.4321/s1130-01082006000200006
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B surface antigen detection using pooled sera: A cost-benefit analysis

Abstract: Objectives: to examine the feasibility and to perform a cost benefit analysis of a 5-sample pooling strategy using an enzyme immunoassay (EIA) for the screening of hepatitis B surface antigen (HBsAg).Material and methods: to assess the sensitivity and specificity of the pooling method, each of the 40 positive sera (from weak to intensely HBsAg-positive) and 250 negative sera were tested in a pool with 4 HBsAg-negative sera. The limit of detection for HBsAg/ad and HBsAg/ay was evaluated using sera from a panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…The current study aimed to investigate pooled sera for HIV and syphilis in blood donors compared to their individual sera to reduce the cost taking into account previous studies that demonstrated pooling was feasible and costeffective even in populations with high prevalence of HBV and HCV infection. 8,9 As far as we know, no previous research has investigated pooling method by ELISA on syphilis. However, in the current study, we chose only 2 parameters HIV and syphilis infection.…”
Section: Discussionmentioning
confidence: 99%
“…The current study aimed to investigate pooled sera for HIV and syphilis in blood donors compared to their individual sera to reduce the cost taking into account previous studies that demonstrated pooling was feasible and costeffective even in populations with high prevalence of HBV and HCV infection. 8,9 As far as we know, no previous research has investigated pooling method by ELISA on syphilis. However, in the current study, we chose only 2 parameters HIV and syphilis infection.…”
Section: Discussionmentioning
confidence: 99%
“…Distribution of HBsAg subtype has been reported in different regions of the world. Fernández et al in Spain reported the ad and ay HBs subtypes amongst 40 chronic HBV patients ( 24 ). De Souza et al from Brazil reported HBsAg subtypes adw2 , adw4 , and ayw amongst patients with mental problems ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been mentioned that in various diseases the presence of antigen without antibody in those who have negative tests may neutralise the positivity in a pool containing positive samples (Raboud et al 1996; Fernández et al 2006). The probability of antibody being neutralised would depend on the strength and concentration of the antigen and the prevalence of antigen in the investigated population.…”
Section: Discussionmentioning
confidence: 99%